The Role of Notaries/PPATs in the Process of Discharging Mortgages (Roya) and Its Implications for Legal Certainty for the Public - Lilis Kori'ah; Ulandari; Nara Purnama Wari (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the role of Notary/Land Deed Official (PPAT) in mortgage right deletion (roya) and its implications for legal certainty. It employs a qualitative socio-legal approach through field research conducted in Way Kanan from February to March 2026. Data were collected through in-depth interviews and documentation and analyzed interactively using the Miles and Huberman model. The findings show that the role of Notary/PPAT is still dominated by administrative functions, while substantive and educational functions remain suboptimal. The dominance of administrative orientation becomes the main cause of the weak educational function of Notary/PPAT, creating a gap between legal norms and practice. Consequently, delays or failure to conduct roya after debt settlement still frequently occur, resulting in legal uncertainty, obstructed land transactions, and limited access to financing. The effectiveness of this role is influenced by public legal awareness, institutional coordination, service bureaucracy, and the professionalism of Notary/PPAT. This study confirms that legal certainty is shaped through the interaction between norms, actors, and social practices.